A high-nuclearity CuI/CuII nanocluster catalyst for phenol degradation. Issue 45 (10th May 2021) - Liu, Li-Juan; Zhang, Jiang-Wei; Asad, Muhammad; Wang, Zhao-Yang; Zang, Shuang-Quan; Mak, Thomas C. W.
Abstract : A high-nuclearity Cu I /Cu II nanocluster catalyst for phenol degradation. Abstract : Herein, we report a 54-nuclei copper nanocluster, [Cu54 S13 O6 ( t BuS)20 ( t BuSO3 )12 ] (Cu54 ), which is the largest atom-precise Cu I /Cu II mix-valent cluster reported. The Cu54 nanoclusters supported by TiO2 exhibit decent photocatalytic activity for phenol degradation under visible light. This work provides a platform to explore the catalytic behaviors of Cu I /Cu II nanosystems.